Validação da versão brasileira da Behavioral Pain Scale em pacientes sedados e em ventilação mecânica invasiva - Santos, Isabela Azevedo Freire (2015)
Pain measurement in Intensive Care Units has received more notoriety just recently due to the need of developing new pharmacological methods and improving pain assessment in critically ill subjects. This assessment can be performed based on validated instruments as the Behavioral Pain Scale (BPS). The difficulty for patients using artificial airway to communicate and the absence of a Brazilian version of a scale for pain assessment in adults mechanically ventilated justifies the relevance of this study that aimed to validate the Brazilian version of BPS as well as to correlate the scores of this scale with the records of physiological parameters, sedation level and disease of this sample. This observational study was conducted in the cardiologic ICU at the Hospital de Cirurgia in Aracaju-Sergipe-Brazil from February to August 2014. Twenty five sedated or unconscious adult patients connected to an artificial airway who were using mechanical ventilation were included in this study. The Brazilian BPS version and the recording of heart rate, blood pressure and peripheral oxygen saturation were performed by two independent investigators simultaneously during three different moments: at rest, during eye cleaning (non-painful stimulus) and during tracheal aspiration (painful stimulus). Other variables as sedation level and severity of disease were recorded by using the Ramsay Scale, Richmond Agitation Sedation Scale (RASS) and APACHE II (Acute Physiology Health Chronic Evaluation) score respectively. The intake of sedative and analgesic medicines during patient assessment was also recorded. The analyzed sample was considered homogeneous despite of the type of surgery and postoperative time duration. It was evidenced high values of responsiveness coefficient (coefficient = 3.22), Cronbach alpha (internal consistency) (Cronbach α= 0.8 during both eye cleaning and tracheal suctioning) and Intraclass Correlation Coefficient (interrater reliability) (ICC= 0.8 during eye cleaning; ICC= 0.9 during tracheal suctioning). As to the validity, changes on BPS score in three assessment moments resulted in significant difference between rest and painful procedure, with the highest score values in this last one (p≤ 0.0001). However, correlations between pain and other variables (hemodynamic parameters, sedation level, and severity of disease) were not significant. Based on these results, the Brazilian BPS version was considered a valid instrument for ICUs in Brazil.